Pregnant Women's Knowledge and Attitudes About Pregnancy Care: The Effect of Using the Ebumil Android Application - Kartini; Farming; Fitriati Sabur (Public Health of Indonesia)
Background: Maternal and infant health is still one of the issues that receive special attention related to improving the quality of human life in the world. Every hour, one woman dies during childbirth or due to causes related to pregnancy. There are still many pregnant women who are less aware of the importance of examination as an effort to detect pregnancy risk factors. Lack of knowledge and attitude, makes pregnant women less aware of the emergence of symptoms of certain dangerous diseases, either indirectly causing maternal death.